1993
DOI: 10.1291/hypres.16.209
|View full text |Cite
|
Sign up to set email alerts
|

The Relation between Sleep Apnea and Intra-Arterially Measured Blood Pressure in Hyperternsive Patients with Sleep Apnea Syndrome.

Abstract: The relationship between sleep apnea and blood pressure was examined in 7 patients with sleep apnea syndrome (SAS). In addition, whether or not SAS is a risk factor for cerebrovascular disease was assessed. Polysomnography, including measurements of arterial 02 saturation (Sa02), was performed in 7 patients during a 3-day hospitalization period; direct intra-arterial blood pressure was continuously recorded. The blood pressure data were analyzed at the beginning of apnea, the beginning of fall in Sa02, the end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Low diastolic pressure and systemic hypertension are reported to be strongly associated with glaucoma [ 4 , 6 , 25 , 26 ]. Some authors suggested that physiological nocturnal hypotension, in the presence of other vascular risk factors, can bring the optic nerve head circulation under the critical levels and thus play a role in the pathogenesis of anterior ischemic neuropathy and glaucoma [ 1 , 10 , 16 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Low diastolic pressure and systemic hypertension are reported to be strongly associated with glaucoma [ 4 , 6 , 25 , 26 ]. Some authors suggested that physiological nocturnal hypotension, in the presence of other vascular risk factors, can bring the optic nerve head circulation under the critical levels and thus play a role in the pathogenesis of anterior ischemic neuropathy and glaucoma [ 1 , 10 , 16 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…SDB including large swings in nocturnal blood pressure (Arimoto et al 1995;Leroy et al 1996;Shepard 1985) and in some cases recurrent severe hypoxia may aggravate anoxic optic nerve damage, which is implicated in glaucoma. According to the literature and our data, in future studies it would be interesting to look for a predictive model (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…It has been established that there are significant changes to the arterial blood pressure between the REM and NREM sleep phases [ 37 ]. Features of PPG that correspond to the changes in arterial blood pressure, such as the area under the PPG cycle, area of systolic and diastolic and the ratio of the systolic and diastolic area (complete list in table 4 ) were extracted from the recordings.…”
Section: Methodsmentioning
confidence: 99%